The effect of sun-dried raisins (Vitis vinifera L.) on the in vitro composition of the gut microbiota. Issue 9 (1st September 2016) - Mandalari, Giuseppina; Chessa, Simona; Bisignano, Carlo; Chan, Luisa; Carughi, Arianna
Abstract : Modulation of the human gut microbiota has proven to have beneficial effects on host health. Sun-dried raisins exhibited prebiotic potential. Abstract : Modulation of the human gut microbiota has proven to have beneficial effects on host health. The aim of this work was to evaluate the effect of sun-dried raisins (SR) on the composition of the human gut microbiota. A full model of the gastrointestinal tract, which includes simulated mastication, a dynamic gastric model, a duodenal model and a colonic model of the human large intestine, was used. An increase in the numbers of bifidobacteria and lactobacilli was observed by plate-counting in response to the addition of either SR or FOS after 8 and 24 h fermentation. A significant decrease in Firmicutes and Bacteroidetes was observed in SR samples after 8 and 24 h fermentation. FOS resulted in the greatest production of short chain fatty acids. Sun-dried raisins demonstrated considerable potential to promote the colonization and proliferation of beneficial bacteria in the human large intestine and to stimulate the production of organic acids.